(untitled) (Research, Society and Development, 2020)
Considering that the market tends to be competitive in the search for better technologies, tools and methodologies to reach their goals, companies have been looking for professionals with profile compatible with the job opportunity of the organization. For this, recruiters can use personality tests as a complement in the selection process, one of these methods is Big Five. Thus, the purpose of this paper was to identify personality traits of students in a course and to compare the traits of incoming students with graduating students. This work was conducted by means of a Survey, in which the necessary data for the research can be obtained. As a result, there was a similarity between the personality traits of incoming students and graduating students. In addition, in terms of extroversion, both have a high level of adherence to this trait, but when it comes to opening new experiences, new entrants are more conservative than seniors.